Development of Spectral Slicing WDM (Wavelength division multiplexing) system - Nur Syazwani Mohamad Radzi (Universiti Malaysia Perlis, 2008)
Multiplexing is the transmission of information from one or more source to one or more destination over the same transmission medium. Although transmissions occur on the same facility, they do not necessarily occur at the same time or occupy the same bandwidth. The transmission medium may be a coaxial cable, a satellite microwave system, or an optical fiber cable. There are several domains in which multiplexing can be accomplished, including space, phase, time, frequency and wavelength. However, the three most main methods of multiplexing signals are time-division multiplexing (TDM), frequency-division multiplexing (FDM), and the more recently developed wavelength-division multiplexing (WDM). Wavelength Division Multiplexing is the technique that allows several different signals to be carried along a single fiber at the same time. It achieves this by using different wavelengths for each transmission and can be employed on single mode or multimode fibers.